2019
DOI: 10.1111/jocn.14821
|View full text |Cite
|
Sign up to set email alerts
|

Adherence assessment practices in haemodialysis settings: A qualitative exploration of nurses and pharmacists' perspectives

Abstract: Aims and objectives. To explore clinician assessment of patient adherence, and identify strategies to improve adherence assessment practices in haemodialysis settings. Background. Patients with chronic kidney disease undergoing haemodialysis are typically prescribed complex regimens; as such, they are at high risk of medication nonadherence. Current clinical practices focus on prescribing medications, however, little attention is paid to measuring and ensuring patient adherence to their prescribed treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Time and resource constraints were also found to challenge comprehensive alignment of medications and treatment goals with patients. These findings resonate with prior studies and re-confirm the recommendation of more systematic medication adherence practices with active patient involvement in hemodialysis settings [6][7][8][9]. Our findings also enrich exciting knowledge by indicating that residents shy away from practicing deprescribing as a tool to support adherence.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Time and resource constraints were also found to challenge comprehensive alignment of medications and treatment goals with patients. These findings resonate with prior studies and re-confirm the recommendation of more systematic medication adherence practices with active patient involvement in hemodialysis settings [6][7][8][9]. Our findings also enrich exciting knowledge by indicating that residents shy away from practicing deprescribing as a tool to support adherence.…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, it seems important to incorporate the patients perspective of adherence in routine care. Ghimire et al suggested implementing checklists and validated questionnaires as a way forward [ 8 ]. We agree with this suggestion, as this approach might enhance the quality of care [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 A unique addition to this study was the provision of concurrent pharmacist access, known to improve adherence by reducing the risk of medication-record discrepancies and medication-related problems. 23 These different interventions targeted various barriers faced by ESKD patients, especially Black patients, including lack of social or emotional support and limited health literacy preventing an in-depth understanding of medications and importance of hemodialysis treatments.…”
Section: Interventionsmentioning
confidence: 99%